2016
DOI: 10.1016/j.beth.2015.09.001
|View full text |Cite
|
Sign up to set email alerts
|

An Empirical Examination of Symptom Substitution Associated With Behavior Therapy for Tourette's Disorder

Abstract: Over the past 6 decades, behavior therapy has been a major contributor to the development of evidence-based psychotherapy treatments. However, a longstanding concern with behavior therapy among many nonbehavioral clinicians has been the potential risk for symptom substitution. Few studies have been conducted to evaluate symptom substitution in response to behavioral treatments, largely due to measurement and definitional challenges associated with treated psychiatric symptoms. Given the overt motor and vocal t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 50 publications
0
9
0
Order By: Relevance
“…While neurocognitive predictors of response to behavior therapy were not identified, youth receiving Comprehensive Behavior Intervention for Tics exhibited significantly reduced tic severity without any diminished cognitive functioning (Piacentini et al, 2010). This is important because some parents and clinicians express concern that implementing behavioral strategies for tics are likely to yield adverse effects on tics and increase the demand on children’s cognitive resources (Burd and Kerbeshian, 1987; Woods et al, 2010; Peterson et al 2016). Thus, these findings provide evidence that behavior therapy does not negatively impact neurocognitive functioning, relative to a non-tic specific treatment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While neurocognitive predictors of response to behavior therapy were not identified, youth receiving Comprehensive Behavior Intervention for Tics exhibited significantly reduced tic severity without any diminished cognitive functioning (Piacentini et al, 2010). This is important because some parents and clinicians express concern that implementing behavioral strategies for tics are likely to yield adverse effects on tics and increase the demand on children’s cognitive resources (Burd and Kerbeshian, 1987; Woods et al, 2010; Peterson et al 2016). Thus, these findings provide evidence that behavior therapy does not negatively impact neurocognitive functioning, relative to a non-tic specific treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Traditionally, pharmacotherapy has been used to manage tic severity with antipsychotic and alpha-2 agonist medications yielding moderate reductions in tic severity (Weisman et al, 2012), although these medications are typically accompanied by adverse side effects and only partial response (Scahill et al, 2006). Meanwhile, behavioral interventions such as habit reversal training (HRT) and the Comprehensive Behavioral Intervention for Tics (CBIT) (Woods et al, 2008) have demonstrated moderate-to-large reductions in tic severity with no significant adverse effects or concerns of symptom substitution (Piacentini et al, 2010; McGuire et al, 2014; Peterson et al, 2016). Despite the proven efficacy of behavior treatments for tics, the neural mechanisms underlying their response remain largely unexamined and the limited neurocognitive research to date has produced mixed findings among youth with Tourette’s Disorder.…”
Section: Introductionmentioning
confidence: 99%
“…For example, if an arm tic was treated with behavior therapy, the concern may be that the patient may develop a new tic (e.g., leg kick) in response to suppressing their original tic and/or experience a worsening in severity of non-targeted tics. Despite possible evidence in among case reports [59, 60], systematic empirical evaluations have found no evidence of symptom substitution in response to behavior therapy for tics for individuals with PTD [62]. …”
Section: Challenges Confronting Behavior Therapy For Ticsmentioning
confidence: 99%
“…Still, some practitioners retain misconceptions about its safety. A report on 228 participants in randomized controlled trials (RCTs) of Comprehensive Behavioral Intervention for Tics (CBIT) helps to confute those concerns 62 . Specifically, CBIT participants were no more likely to have new tics, have adverse events, increase tic medications or have an exacerbation in psychiatric symptoms relative to patients who received supportive therapy.…”
Section: Resultsmentioning
confidence: 99%